2016
DOI: 10.1021/acs.inorgchem.6b01467
|View full text |Cite
|
Sign up to set email alerts
|

AlFe2–xCoxB2 (x = 0–0.30): TC Tuning through Co Substitution for a Promising Magnetocaloric Material Realized by Spark Plasma Sintering

Abstract: AlFeB and AlFeCoB (x = 0-0.30) were synthesized from the elements in three different ways. The samples were characterized by powder X-ray diffraction, Rietveld refinements, energy-dispersive X-ray spectroscopy, and magnetic measurements. Using Al flux the formation of AlFeB single crystals is preferred. Arc melting enables the substitution of ∼6% Co. This substitution of Fe by Co decreases the Curie temperature T from 290 to 240 K. The highest Co substitution up to 15% is achieved by spark plasma sintering (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 26 publications
4
46
0
Order By: Relevance
“…This was confirmed using neutron diffraction where a canted antiferromagnetic ordering (below 390 K) was found with the magnetic moments oriented either between the a or c-axes with a doubling of the crystallographic unit cell in the c-direction [22]. By substituting iron on the transition metal site in AlFe 2 B 2 with cobalt, the T C decreases linearly with increasing cobalt concentration, down to 205 K for 30% substitution [23]. ∆S mag did not, however, change significantly with the substitution.…”
Section: Introductionmentioning
confidence: 66%
“…This was confirmed using neutron diffraction where a canted antiferromagnetic ordering (below 390 K) was found with the magnetic moments oriented either between the a or c-axes with a doubling of the crystallographic unit cell in the c-direction [22]. By substituting iron on the transition metal site in AlFe 2 B 2 with cobalt, the T C decreases linearly with increasing cobalt concentration, down to 205 K for 30% substitution [23]. ∆S mag did not, however, change significantly with the substitution.…”
Section: Introductionmentioning
confidence: 66%
“…A Mössbauer study on arc-melted and annealed sample has reported the Curie temperature of 300 K [2]. At the lower limit, the Curie temperature of spark plasma sintered AlFe 2 B 2 was reported to be 274 K [7]. The reported saturation magnetic moment also manifests up to 25% variation from the theoretically predicted saturation moment of 1.25 µ B /Fe.…”
Section: Introductionmentioning
confidence: 92%
“…[18] Te tragonal Ti 3 Co 5 B 2 (space group P4/mbm,n o. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The crystal structure of the ternary variants is formed by face-connected trigonal, tetragonal, andp entagonal prisms of T/T'-atoms (electron-rich transition metals such as Co, Rh, Ir,R u). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The crystal structure of the ternary variants is formed by face-connected trigonal, tetragonal, andp entagonal prisms of T/T'-atoms (electron-rich transition metals such as Co, Rh, Ir,R u).…”
Section: Introductionmentioning
confidence: 99%